Planning and management of irrigation in Sub-Saharan Africa: reducing the environmental and health costs - McCartney, Matthew P.; Boelee, Eline; Cofie, Olufunke O.; Mutero, Clifford M. (2008)
Development of irrigation can result in negative environmental and human health impacts. Irrigation undertaken without full consideration of these impacts can have serious adverse repercussions, not only undermining the investment but also worsening poverty and contributing considerably to peoples? suffering. The impacts are strongly inter-linked because it is changes in the environment that cause changes in health. Furthermore, mitigation measures that reduce environmental damage often improve health outcomes. In the past, research into impacts, and the development of impact assessment methodologies, has focused primarily on large scale, capital intensive, schemes. However, small scale and less formal water management interventions, which are increasingly prevalent in Sub-Saharan Africa, can also have significant environmental and health impacts. This paper summarizes the findings of a study of environmental and health issues associated with all scales of irrigation in Sub-Saharan Africa. It is not a compendium of data, but rather provides an overview and framework for understanding policy and programming issues. It is recommended that a pragmatic approach to address current environmental and health planning includes three levels of implementation: i) strategic planning at the national and regional level; ii) full environmental and health assessment for government and donor funded projects; and iii) development of simplified tools for impact assessment relevant to community led, NGO and small private projects.